Dynamic viscoelasticity of silica-filled styrene-butadiene rubber/polybutadiene rubber (SBR/BR) elastomer composites. (15th April 2020) - Yoon, Bumyong; Kim, Ji Yeon; Hong, Uiseok; Oh, Min Kyeong; Kim, Munsung; Han, Sang Bae; Nam, Jae-Do; Suhr, Jonghwan
Abstract: In this study, the viscoelastic master curve allowed us to explore the effect of silica filler network and bound rubber along with the strain- and temperature-dependent viscoelastic properties. It was experimentally found along with analytical modelling that the bound rubbers improve the damping properties of the elastomer composites in the low frequency range (57%) while reducing damping properties (45%) in the high frequency range. This result indicates that the damping properties can be designed by controlling the bound rubber content in the elastomer composites, which is becoming substantially important for many structural parts such as bush or tire for electric vehicles.